Differential regulation of calcium-activated plant kinases in Arabidopsis thaliana - Zauser, Martin; Liese, Anja Katarina Claire; Feldman-Salit, Anna; Krebs, Melanie; Schumacher, Karin; Romeis, Tina; Kummer, Ursula; Pahle, Jürgen (The plant journal, 2025)
The decoding of calcium signals by plant calcium-dependent kinases (CPKs) is not fully understood yet. Based on kinetic in vitro measurements of the activity of several CPK proteins, their individual activity profile was modeled and coupled to cytosolic calcium concentration changes from in vivo measurements of guard cells and epidermal leaf cells. In addition, computationally produced surrogate data were used. It was analyzed how individual activity profiles of CPKs will change in response to the different calcium time courses. In addition, the impact of modeling explicitly individual elementary reaction steps for binding and unbinding in comparison to using a heuristic Hill equation for the binding process was investigated.